Improving Student Learning Outcomes Using Problem-Based Learning Models in PAI Class IV UPTD Elementary School 06 Batang Timbulan - Ella Astia (BiCED Proceeding, 2024)
This study aims to improve students' learning outcomes in Islamic Religious Education (PAI) by applying the Problem Based Learning (PBL) model in class IV at UPTD SD Negeri 06 Batang Timbulan. The research was conducted in two cycles, each involving planning, implementation, observation, and reflection adjusted to enhance the effectiveness of learning. The results showed that the PBL model improved student engagement in learning and better formative test results. In the first cycle, there was an improvement, but some challenges such as limited time for discussion and group cooperation difficulties needed to be addressed in the second cycle. With improvements made in the second cycle, students' learning outcomes showed significant progress. This study concludes that PBL is effective in enhancing students' understanding of PAI material and developing their critical and creative thinking skills.